A study of the effect of OHSAS 18001 on the occupational injury rate in Iran. Issue 1 (2nd January 2017) - Ghahramani, Abolfazl; Summala, Heikki
Abstract : The occupational health and safety management system (OHSMS) has been a widely used approach for managing occupational health and safety more effectively worldwide. Despite the interest of organizations in implementing OHSMS in recent decades, few studies have examined the effectiveness of these interventions. This study presents an empirical investigation of the effect of occupational health and safety assessment series (OHSAS) 18001 as a worldwide-accepted OHSMS on the occupational injury rate (OIR) in Iran. This study was carried out in six companies: three OHSAS 18001-certified, and three non-certified, including 998 occupational injuries for 15, 842 person-months. A before–after analysis showed a positive safety performance change in one out of the three certified companies. For all 66 study years in the six companies, a negative binomial regression did not indicate a lower occupational injury during the certified years and a repeated measures analysis of variance (ANOVA) did not confirm the effect of certification. The results of this study indicated that the implementation of OHSAS 18001 is not a guarantee of improved safety.